Survival analysis of faith students using product-limit estimation and Nelson-Aaslen estimation - Aala, Mylen L.
This study focuses on the survival of FAITH students in their respective courses, with the objective of estimating the average length of time that a student spend in his/her course. Graduation and withdrawal decrements are considered. Estimates of the survival function in the double-decrement environment are obtained using Product-Limit Estimation and Nelson-Aalen Estimation. The estimates are compared to determine the better approximation procedure.